EFFECT OF TWO ATMOSPHERES PACKAGING ON EDIBLE MUSHROOMS (Pleurotus ostreatus L.) TREATED BY VACUUM IMPREGNATION WITH CONSERVANT SOLUTION - RUIZ, Marilsa P.; CORTÉS, Misael; HENRÍQUEZ, Luis E. (Vitae, 2010)
In this paper the vacuum impregnation technique (IV) is applied on edible whole mushroom (Pleurotus ostreatus L.) using a conservant solution (CS) containing ascorbic acid, citric acid, salt, low metoxyl pectin and calcium, to develop a minimally processed product. The response to the impregnation is appraised to determine the composition of CS and to evaluate changes in the physiochemical, microbiological and sensorial characteristics of the impregnated matrix stored at 4ºC in two atmospheres during 12 days packaging. The volumetric fraction of impregnation in small (5.5 ± 1.4 g) and big mushrooms (12.2 ± 2.2 g) is respectively of 39.7 ± 8.6% and 31.2 ± 10.7%. The physicochemical parameters are affected for CS, the time of storage and the packaging atmosphere. The ºBrix, % acidity, % chlorides and% humidity decrease, the pH rises and the aw keeps uniform during that time. CS allows to control the browning, obtaining a product with an acceptable color until the ninth day. The brightness (L*) shows a tendency to decrease with the time (darker), but keeping it in the chromatic plane a*b* in the gray areas. The texture of the product is considered acceptable with elastic characteristic and CS maintains it during the time. For both atmospheres, the microbiological parameters are within the acceptable limits in the Colombian norm. The IV process represents an effective methodology that improves the sensorial, microbiological and quality attributes of the mushroom increasing 12.5% the shelf life.